Study protocol for a randomised controlled trial of a virtual antenatal intervention for improved diet and iron intake in Kapilvastu district, Nepal: VALID - Joanna Morrison; Hassan Haghparast-Bidgoli; Shraddha Manandhar; Andrew Copas; Helen Harris-Fry; Naomi M Saville; Sanju Bhattarai; Santosh Giri; Bibhu Thapaliya; Abriti Arjyal; Sushil C Baral; Sara Hillman (BMJ Open)
Introduction Despite evidence that iron and folic acid (IFA) supplements can improve anaemia in pregnant women, uptake in Nepal is suboptimal. We hypothesised that providing virtual counselling twice in mid-pregnancy, would increase compliance to IFA tablets during the COVID-19 pandemic compared with antenatal care (ANC alone.Methods and analysis This non-blinded individually randomised controlled trial in the plains of Nepal has two study arms: (1) control: routine ANC; and (2) ‘Virtual’ antenatal counselling plus routine ANC. Pregnant women are eligible to enrol if they are married, aged 13–49 years, able to respond to questions, 12–28 weeks’ gestation, and plan to reside in Nepal for the next 5 weeks. The intervention comprises two virtual counselling sessions facilitated by auxiliary nurse midwives at least 2 weeks apart in mid-pregnancy. Virtual counselling uses a dialogical problem-solving approach with pregnant women and their families. We randomised 150 pregnant women to each arm, stratifying by primigravida/multigravida and IFA consumption at baseline, providing 80% power to detect a 15% absolute difference in primary outcome assuming 67% prevalence in control arm and 10% loss-to-follow-up. Outcomes are measured 49–70 days after enrolment, or up to delivery otherwise. Primary outcome: consumption of IFA on at least 80% of the previous 14 days. Secondary outcomes: dietary diversity, consumption of intervention-promoted foods, practicing ways to enhance bioavailability and knowledge of iron-rich foods. Our mixed-methods process evaluation explores acceptability, fidelity, feasibility, coverage (equity and reach), sustainability and pathways to impact. We estimate costs and cost-effectiveness of the intervention from a provider perspective. Primary analysis is by intention-to-treat, using logistic regression.Ethics and dissemination We obtained ethical approval from Nepal Health Research Council (570/2021) and UCL ethics committee (14301/001). We will disseminate findings in peer-reviewed journal articles and by engaging policymakers in Nepal.Trial registration number ISRCTN17842200.